شیكردنەوەی جوگرافی بۆ بەكارهێنانی زەوی لە شاری دوكان لەنێوان ساڵی 2002-2020 - حسین, پ.ی.د.بەیان علی; عبداللە, م.ی. هەورامان كمال میرزا (Sulaimani Journal for Humanities, 2023)
The landusing is one of the main fields in the urban geography because the cities are in a permanent expansion as a result of the continues population increase in the cities, which may lead to a pernail demand for different kinds of services and endless enlargement of their amounts. All these changes in the world lead to a significant change in the sizes and the rates of the different types of landings inside the cities, and as a result of these changes the cities would make changes in the cities, shapes and their morphology. The researches that studying the different types of landusing inside the cities are occupying a high rank in the studies that deals with the city’s morphology and its structure. The expansion of the city’s area on other lands will reflect its influence on the city’s morphology and its structure, which makes the external appearance of any city. The external appearance is the main phenomenon that distinguish any city from its surroundings. The main aim of this study is to recognize the changes that occur to the different sorts of landuse inside Dukan city, especially these changes that happened to the cadastral map of this city. The study also tries to recognize that causes that stand behind these changes, and that would be helpful for those who are in charge of putting the plans to deal with the problems for future in order to find appropriate solution for those problems concerning the landusing in the city of Dukan. To achieve the main goals of the study, the researcher tries to use “analysis and comparative methods” to meet the essential goals of the study. The study has been divided to two main branches. The first one examines the landuse in Dukan city in 2002. The second branch deals with the landuse in Dukan city during the year of 2020. Finally, the research reaches to some conclusions that the transportation services occupies the largest section of the landusing for the all purposes in this city during that period of time. The other conclusion is: the landusing for the religious purposes occupies the smallest size on the cadastral map of Dukan city. The researches, at last, shows some suggestions in order to make a balance between the sizes of different sort of landuses for different purposes, by depending on the standards known as “urban planning” Finally, the study also urges the authorities to more attention to the tourism which makes the identity to the Dukan city.